Digital Assistive Technologies and Their Effectiveness in Supporting Students with Visual Impairments in Online Learning Environments - Al Hadid, Shama yahaya Bader (Journal of Ecohumanism, 2025)
This research seeks to examine the efficiency of Digital Assistive Technologies (DATs) in assisting the visually impaired students in a learning environment that is online. Twenty visually impaired university students in distance learning programs were used as the sample. The methodology used was descriptive quantitative and involved a structured questionnaire that was aimed at evaluating five different domains, namely the types of DATs used, satisfaction, usability, academic impact, and perceived inclusivity. The data was analyzed with means, standard deviations, and one sample t-tests. The findings indicated that the most used technologies were screen readers (M = 4.10, SD = 0.64) and magnifiers (M = 3.95, SD = 0.89). The students expressed great satisfaction with DATs (M = 3.81, SD = 0.34) and ease of use (M = 3.84, SD = 0.55). The perceived academic performance was also very high, with an increase in speed of assignment completion (M = 3.90, SD = 0.27) and academic performance (M = 3.96, SD = 0.34). Also, the students strongly agreed that DATs improved their educational autonomy (M = 3.88, SD = 0.36) and were important in inclusive education (M = 4.00, SD = 0.30). The mean values of all the significant variables were very high above the neutral score of 3 (p < .001), showing that the positive perceptions of DATs in digital learning contexts have been widespread.